A Thienyl‐Substituted Diketopyrrolopyrrole Derivative with Efficient Reactive Oxygen Species Generation for Photodynamic Therapy. Issue 6 (20th May 2016) - Shi, Huaxia; Sun, Wucheng; Wang, Qiang; Gu, Guiying; Si, Weili; Huang, Wei; Zhang, Qi; Dong, Xiaochen
Abstract: Reducing the energy gap of photosensitizer between singlet and triplet states (Δ E ST ) can improve the efficiency of intersystem crossing, further enhancing the resulting generation of reactive oxygen species for photodynamic therapy. In this study, two photosensitizer chromophores—phenyl‐substituted diketopyrrolopyrrole and thienyl‐substituted diketopyrrolopyrrole (TDPP)—were synthesized. Theoretical calculations indicate that TDPP can greatly reduce the Δ E ST (0.48 eV) relative to that of diketopyrrolopyrrole (0.66 eV). Experiments confirmed that TDPP generates reactive oxygen species more efficiently than diketopyrrolopyrrole. After conjugation of TDPP with methoxy poly(ethylene glycol)carboxyl (mPEG‐COOH), the resulting TDPP‐mPEG has excellent water solubility, biocompatibility and photostability. When it serves as photosensitizer for photodynamic therapy, in vitro and in vivo measurements indicate that TDPP‐mPEG can effectively inhibit tumor growth and shows great potential for the treatment of cancer in the clinic. Abstract : Impact sub : Thienyl substituents on diketopyrrolopyrroles (TDPPs) are considered to be more efficient at π‐conjugation than phenyl substituents, reducing the band gap between singlet and triplet states. This can greatly facilitate intersystem crossing and enhance the generation of reactive oxygen species. TDPP conjugated with methoxy poly(ethylene glycol) has excellent water solubility, biocompatibility and photostability, and significantly inhibited tumor growth upon irradiation with light.